PENGARUH SISTEM PENGENDALIAN INTERN, KOMITMEN ORGANISASI, DAN TINGKAT PENGAWASAN KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH KABUPATEN GIANYAR - Yani Ni Wayan Indah (UNHI Press, 2022)
This research was conducted with the aim of whether the internal control system, organizational committee and level of regional financial supervision have an influence on the quality of the financial statements of the Gianyar Regency local government. Of the 5,224 population who work in the OPD of Gianyar Regency, 128 samples were used in this study because they met the criteria set out in this study. From the results of the data that has been obtained after conducting research in the field, further testing is carried out with the help of the SPPS 21 test, namely the Multiple Linear Regression Test. After the test, the results showed that the Internal Control System and Organizational Commitment had an influence on the quality of regional government financial reports, while the Regional Financial Supervision Level had no effect on the Quality of the Gianyar Regency Government's Financial Reports.